2014
DOI: 10.1063/1.4901919
|View full text |Cite
|
Sign up to set email alerts
|

X-ray conversion efficiency and radiation non-uniformity in the hohlraum experiments at Shenguang-III prototype laser facility

Abstract: The hohlraum radiation properties are studied experimentally by the Shenguang-III prototype laser facility and numerically by the two-dimensional code LARED with the multi-group radiation transfer model. The measured radiation temperature is consistent with the prediction of the simulations in a wide laser energy range, suggesting that the x-ray conversion efficiency is around 75% at the peak radiation temperature. The delicate hohlraum experiments further show that the radiation intensity inside the hohlraum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…In the simulation, the scattered light energy of Au hohlraum is set as 8% of the total laser energy. This value was obtained from previous Au hohlraum energetic experiments on SGIII-prototype [27], in which the total laser energy and T r are similar to those of our comparative experiment. As the scattered laser energy of UN-coated DUH has not been measured yet, we assume it to be 8%, considering the same laser and similar plasma conditions as Au hohlraum.…”
Section: Results and Analysissupporting
confidence: 85%
“…In the simulation, the scattered light energy of Au hohlraum is set as 8% of the total laser energy. This value was obtained from previous Au hohlraum energetic experiments on SGIII-prototype [27], in which the total laser energy and T r are similar to those of our comparative experiment. As the scattered laser energy of UN-coated DUH has not been measured yet, we assume it to be 8%, considering the same laser and similar plasma conditions as Au hohlraum.…”
Section: Results and Analysissupporting
confidence: 85%
“…The experimental results [48,49] indicated that the ratio of the flux from the laser spots and the wall was varying with time, and reached a peak value of about 2. The flux ratio was defined by the time-dependent wall albedo (the ratio of the re-emitted flux to the incident flux on the wall), which was taken from [37].…”
Section: Drive Symmetrymentioning
confidence: 99%
“…For comparison, the diameter of the capsule and the LEHs are fixed at 2.2 mm [9] and 2.4 mm (as stated in section 2), respectively. According to the experimental results and theor etical studies [47][48][49], the ratio of the peak flux from laser spots and the wall is taken as 2, similar to the treatment of [43]. To optimize the initial parameters of the hohlraum [50], the variations of the root-mean-square (RMS) [51] of the peak drive asymmetry as the length of the half cylinder with different cavity-to-capsule ratios (CCR = 2.0-2.5) [37], were simulated by IRAD3D, as shown in figure 2.…”
Section: Drive Symmetrymentioning
confidence: 99%
“…Even though the ViewFactor experiments 10 at NIF facilitate a direct diagnosis of the X-ray drive from the capsule point of view, because of the challenge outlined earlier, realizing accurate space-resolving flux detection inside the hohlraum in these experiments is still difficult. The creation of additional diagnostic holes on the hohlraum wall has been attempted to measure the laser spot and re-emitting wall fluxes 11 . Nevertheless, the hole closure effect 10 , 12 and the change in the hohlraum structure caused by the opening of diagnostic holes could seriously affect the flux results.…”
Section: Introductionmentioning
confidence: 99%